Murine models for studying immunopathogenesis in gastrointestinal lesions: How to go about it - Neharika Jain (Wolters Kluwer Medknow Publications, 2021)
Gastro-intestinal (GI) lesions are common outcome to diverse etiological agents affecting the GI tract. It requires significant expertise to accurately diagnose the fundamental cause and treat accordingly. A better understanding of the immunological underpinning of these lesions is of great importance to ensure their successful management. Availability of specific animal models allows us to understand the subtle differences among diverse disease conditions and help decide upon the treatment trajectories. Since murine models are best suited for studying the immunopathogenesis of any disease, we will restrict our discussions here to the available murine models and their applications to study gastrointestinal lesions. In this review, we have systematically examined and compared the variety of mice models that are routinely used to study Inflammatory Bowel disease (IBD) and also how they can be leveraged to address specific questions relating to IBD.